Project-Based Learning as a Catalyst for Creativity Development in Integrated Science and Social Studies at Primary Level - Arif Khamidah; Ana Fitrotun Nisa (Papanda Publisher, 2026)
In the era of Kurikulum Merdeka, creativity remains a critical yet underdeveloped competency in elementary Ilmu Pengetahuan Alam dan Sosial (IPAS) learning, often limited by conventional methods. Project-Based Learning (PjBL) offers a promising approach to foster creative thinking through authentic, inquiry-driven projects. This qualitative descriptive study involved 28 fifth-grade students at SDN Rejowinangun 1, Yogyakarta, during May 2025. Data were collected via observation, semi-structured interviews, documentation of project artifacts, and a creativity rubric assessing fluency, flexibility, originality, and elaboration. Analysis followed Miles and Huberman's interactive model. PjBL implementation in a solar system arrangement project significantly improved creativity, with post-intervention modal score of 4 (very creative) at 42%. Students showed increased idea generation, collaborative innovation, and detailed elaboration, alongside high engagement and unexpected creative deviations. Findings align with constructivist and cooperative learning theories, extending prior evidence on PjBL in science education to integrated IPAS contexts. The model effectively bridges knowledge gaps in Kurikulum Merdeka implementation.